Mg-Zn-Ca amorphous alloys for application as temporary implant: Effect of Zn content on the mechanical and corrosion properties. (15th November 2016) - Matias, T.B.; Roche, V.; Nogueira, R.P.; Asato, G.H.; Kiminami, C.S.; Bolfarini, C.; Botta, W.J.; Jorge, A.M.
Abstract: In this paper, two Mg-Zn-Ca amorphous alloys were processed and their mechanical and corrosion properties were evaluated and compared. The first alloy was a new composition, Zn-rich, Mg60 Zn34 Ca6, designed thanks to a multifold approach involving two different criteria, topological instability, and electronic criteria. The second alloy, with less Zn content, was a well-known Mg73 Zn23 Ca4, used for the sake of comparison. Three kinds of rapidly solidified samples were processed for each composition: ribbons, wedge, and cylindrical samples. The new composition showed much better glass-forming ability and superior corrosion and mechanical properties than the Zn-poorer composition. The effect of Fe content, a typical contaminant in Mg-based alloys, was also evaluated. Electrochemical results in amorphous and in crystalline samples showed that increasing iron to certain amounts has no influence on the corrosion resistance of the investigated alloys. Graphical abstract: Highlights: A new amorphous composition Mg60 Zn34 Ca6 alloy was designed using a multifold approach involving two different criteria; A well-known composition, Zn-poor, Mg73 Zn23 Ca4, was used for the sake of comparison; Increasing Zn improved glass forming ability, hardness and corrosion properties. Zn-poor composition was microalloyed with iron to study its effects (contamination) on the corrosion properties. Fe contamination up to 410 ppm was not deleterious for corrosion properties of amorphous or crystalline samples.